Inovasi Perangkat Layanan Bimbingan Klasikal Untuk Meningkatkan Sikap Jujur Pada Siswa - Dewi Silviana; I Ketut Gading; Kadek Ari Dwiarwati (Universitas Pendidikan Ganesha, 2022)
This study aims to develop and test the acceptability of classical guidance service tools to increase honesty in junior high school students. The model that is used as a reference in this classical guidance service development research is the 4D model proposed by Thiagarajan which consists of 4 stages, namely define, design, develop, and distribute. This classical guidance service tool innovation was created to assist counseling guidance teachers in increasing students' honesty in providing counseling guidance services in schools. The results of this study indicate that the classical guidance service tool is said to be valid by involving 5 experts. The effectiveness test of the classical guidance service was carried out with a total of 31 students using the pretest-posttest control group design. Calculation of the T-test obtained a high significance value. Thus, the classical guidance service tool is effective in increasing students' honesty.